KEUNGGULAN KOMPETITIF DAN KOMPARATIF KOMODITI JAGUNG PIPIL DI MINAHASA SELATAN - Winda T. Karaeng; Paulus A. Pangemanan; Celsius Talumingan; Jean F.J. Timban (COCOS, 2014)
ABSTRACTWinda Trisnawati Karaeng. Competitive and Comparative Advantages of Corn Commodity in South Minahasa Regency, Under guidance of Dr. Ir. Paul A. Pangemanan, MS as a Chairman, Ir. Celsius Talumingan, MP and Jean F. J. Timban, SP, MSi as Members.The objective of this research is to analyze competitive and comparative advantages of corn commodity in South Minahasa. The research had been done for two months, start from April 2014 until May 2014. Location of this research was Paslaten Satu Village at Tatapaan Sub District, North Sulawesi Province. Data used in this research was from primary and secondary data. Primary data was from interviews with respondents by used a list of questionaire. While the secondary data was from the relevant departments, such as Agricultural Service, Industrial Service and Statistical Centre Department.The research result showed that corn commodity in South MinahasaRegency has advantages using calculations of Private Profitability (137,159) and Social Profitability (68,139). It means that the corn commodity was efficient and had both competitive advantage and comparative advantage. Two indicators for measure competitiveness were 1) Private Cost Ratio (PCR) show that the corn farmer’s is more competitive because PCR < 1, and 2) Domestic Resources Cost Ratio (DRCR) show that the corn commodity has comparative advantage because DRCR < 1. It means that the corn commodity according to financial analysis was efficient and has greater potency in international trade.